Introduction of a mobile device based tertiary survey application reduces missed injuries: A multi-center prospective study - Moffat, B.; Vogt, K.N.; Inaba, K.; Demetriades, D.; Martin, C.; Malthaner, R.; Gray, D.K.; Parry, N.G. (Injury, 2019)
•First paper to our knowledge to report an app designed to reduce missed injuries.•Significant decrease in missed injuries at all centers following implementation of the app.•Improved completion of tertiary surveys following implementation of the app. Missed injuries during the initial assessment are a major cause of morbidity after trauma. The tertiary survey is a head-to-toe exam designed to identify any injuries missed after initial resuscitation. We designed a novel mobile device application (Physician Assist Trauma Software [PATS]) to standardize performance and documentation of the tertiary survey. This study was undertaken to assess the feasibility of introducing PATS into routine clinical practice, as well as its capacity to reduce missed injuries. Prior to implementation of PATS, the missed injury rates at a higher-volume and a medium-volume level I trauma center were assessed. The PATS program was implemented simultaneously at both centers. Missed injuries were tracked during the study period. Compliance and tertiary survey completion rates were evaluated as a marker of feasibility. At the higher-volume trauma center, the missed injury rated decreased from 1% to 0% with the introduction of the PATS program (p = 0.04). At the medium-volume trauma center, the missed injury rate decreased from 9% to 1% (p < 0.001). Compliance and documentation increased from 68% to 100%, and from no formal documentation to 60% compliance at the higher- and medium-volume centers respectively. The implementation of a mobile tertiary survey application significantly reduced missed injuries at both a higher- and medium-volume trauma center. The use of this application resulted in a significant improvement in compliance with documentation of the tertiary survey.